Management's guide to marking decisions about information systems - Gray, Paul (Wiley, 2006)
This book provides the concepts and tools needed to make managerial decisions about IS within a firm. The focus is on applications rather than technology or techniques and has a managerial orientation, making it a good tool for MBA students.